Surgical treatment of Arnold-Chiari malformation type I in an adult patient - Marković Marko; Berisavac Iva; Bojović Vladimir; Kostić Bojan; Đulejić Vuk (Vojnosanitetski Pregled)
Background. Herniation of the cerebellar tonsils through the foramen magnum into the cervical spinal canal with obliteration of the cerebellomedullary cistern is the primary feature of Arnold-Chiari type I malformation (ACM I). It is considered to be congenital malformation, although there have been reported cases of an acquired form. Case report. We presented a female patient, 45-year old, with ACM I without syringomyelia as a rare and unusual clinical image, as well as the effect of decompressive surgery in the treatment of this malformation. The patient was admitted to the Department of Neurosurgery with clinical signs of truncal ataxia worsening during the last six years. Moderate quadriparesis with predominant lower extremity involvement and the signs of the cranial nerves damages occured during the last seven months before admission, with progressive clinical course up to the date of admission. Neurosurgical treatment that included suboccipital medial craniectomy with resection of posterior arch C1 vertebrae and C2 laminectomy resulted in a significant clinical improvement and a much better quality of life. Conclusion. Posterior craniovertebral decompression with microsurgical reduction of the cerebellar tonsils and placement of an artificial dural graft is a treatment of choice in severe forms of ACM I without syringomyelia. .